POLITENESS PRINCIPLES IN TRADITIONAL MARKET INTERACTIONS - Syarifudin Syarifudin; Afif Ikhwanul Muslimin (ELITE JOURNAL, 2019)
This research outlines how the interaction among Javanese women takes place in traditional markets from a linguistic stand point. It aims primarily at describing the politeness principles in the speech of Javanese women taking place at Karangploso traditional markets in Malang city, East Java Province. There is evidence that women dominate the interaction of selling and buying that occurs in traditional markets considering their role in the domestic domain. The speech act of Javanese women in traditional markets in Malang city was analyzed based on Leech’s politeness principles. These principles consist of six maxims namely generosity maxim, tact maxim, approbation maxim, agreement maxim, modesty maxim, and sympathy maxim. The Javanese women’s speeches were classified on the basis of all of the maxims’ characteristics. The method used is a qualitative method in accordance with Bodgam and Tailor theory. The results showed that all maxims of politeness principles were found in the interaction involving women in traditional markets in Malang city. More importantly, the use of high Javanese language as a means of communication containing the realization of politeness principles may reduce the probability of verbal abuse occurring in the interaction among Javanese women in Kaarangploso traditional markets in Malang city.